Evaluation of the Acoustic Impact of the Public Road Network on a Nature Conservation Area: A Case Study - Jordan Wilk; Joanna Szyszlak-Bargłowicz; Tomasz Słowik; Przemysław Stachyra; Grzegorz Zając (Applied Sciences)
Despite the formal protection of many natural areas, the problem of noise pollution poses a serious challenge to the preservation of their ecological integrity and biodiversity. Traffic noise generated by vehicle traffic on public roads disrupts natural biological processes, negatively affecting animals and the quality of the audiosphere. This research aimed to assess the acoustic impact of the public road network crossing the Roztocze National Park (RPN, Poland) and to characterize noise propagation as a factor polluting the environment and disrupting the functioning of natural forest ecosystems. The equivalent sound pressure level (LAeq) was measured at different distances from four public roads crossing the park. A terrain analysis was also taken into account to determine the impact of height differences on sound propagation. To enhance the acoustic analysis, recordings of environmental sounds were made, and their components, including both natural and anthropogenic sounds, were identified. It was found that traffic noise dominated natural sounds at distances 250 m from roads. The results obtained indicate the need for an integrated approach to protected area management, including noise monitoring, the implementation of noise protection regulations, and environmental education.